Pendekatan Pemuda dalam Transformasi Konflik Rumah Ibadah di Kota Cilegon - Utami, Tia Mega; Lestari, Dwi Puji (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2025)
The ongoing rejection of the construction of the Huria Kristen Batak Protestan (HKBP) Maranatha Church in the Cikuasa neighborhood, Gerem Subdistrict, Grogol District, Cilegon City, remains a pressing issue. According to data from the Central Bureau of Statistics (2024), the non-Muslim population in the area numbers in the thousands, comprising 7,072 Protestants, 1,885 Catholics, 248 Hindus, 1,688 Buddhists, and 10 Confucians. The Muslim majority comprises 459,474 individuals. Despite this religious diversity, not a single house of worship, such as a vihara, temple, shrine, or church, has been permitted to stand in Cilegon City. This study employs Johan Galtung’s theory of conflict transformation to analyze how youth-led initiatives can foster efforts toward conflict transformation. The research adopts a qualitative, descriptive-narrative approach, with data collected through literature studies. The findings reveal that the conflict surrounding places of worship in Cilegon reflects deeply entrenched structural and cultural issues. Youth possess significant potential as agents of change and peacebuilders in the process of conflict transformation. Youth-based approaches are vital in assisting conflicting parties in identifying appropriate strategies for conflict resolution and in building long-term, harmonious relationships. Drawing upon Johan Galtung’s theory of conflict transformation, this study recommends enhancing the capacity of youth as peacemakers through youth empowerment and peace education. Such efforts can contribute to the development of an inclusive society that upholds the values of humanity, unity, and peace.